Effectiveness Of Sweet Star Fruit Juice (Averhoa Carambola) On The Reduction Of Blood Pressure In The Elderly With Hypertension At The Jatirejo Karanganyar Elderly Post - Febria Reza Kurnia; Lingga Kusuma Wardani (Journal of Health Science Community, 2023)
Hypertension is a condition where there is a chronic increase in blood pressure in a very long period of time which can cause pain to someone who is suffering and can cause death. A person can be said to suffer from hypertension if the systolic blood pressure is > 140 mmHg and diastolic > 90 mmHg. Treatment of high blood pressure can be done pharmacologically or by using drugs and non-pharmacological therapy or therapy without drugs. Sweet star fruit is useful in helping to lower blood pressure because of the fiber, potassium, phosphorus and vitamin C content. Water content, magnesium and potassium and high fiber in sweet star fruit can neutralize and lower blood pressure. This research uses the method Pra-Eksperimen One Groups Pretest-Posttest Design. The research population is all elderly at the elderly post in Jatirejo Village, the research sample is 30 people with techniques Purposive Sampling. Based on the research, the average systolic value before the intervention was 150.67 mmHg and the average value in diastole was 97.67 mmHg, after the intervention the average systolic value was 137.33 mmHg and the average value in diastole was 92.67 mmHg. There was a difference in blood pressure after administration of sweet star fruit juice with a p-000 value meaning p <0.05 in systolic and diastolic blood pressure.